PENGARUH BUDAYA KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP KINERJA PROYEK KONSTRUKSI - Reza Muafiq (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2021)
A project is an activity intended to achieve a certain final result which is quite important for the benefit of management. One of them is construction projects, work accidents in the construction sector are still a problem of work safety both in the world and in Indonesia which require attention from various parties. The construction industry is in the first rank of the most dangerous jobs in the world. Meanwhile, K3 plays an important role in minimizing the number of accidents. This research was conducted to identify and analyze the factors that influence the culture of safety and health, especially in construction projects, and to analyze the influence of occupational safety and health cultural factors on the performance of construction projects. The results showed that simultaneously and partially the independent variables consisting of Top Management's Commitment to K3 (X1), K3 Rules and Procedures (X2), Worker Communication (X3), Worker Competence (X4), Work Environment (X5), and Engagement Workers in K3 (X6) have a significant effect on the Construction Project Performance variable (Y).